Relações Públicas em Pose: identificação das estratégias de comunicação de causas e Relações Públicas em Pose - Baraúna, Daniel Nathan Figueiredo (Brasil, 2024)
Understanding the terms homophobia, prejudice and violence is crucial to understanding the sociocultural and political dynamics in the life experience of marginalized LGBT, black and Latino communities. Despite the rights achieved over the years, the debate on this subject is of great importance to understand and recognize where the society failed in terms of public policies to guarantee the rights of such communities. In this context the work analyzes the FX Network series Pose, exploring various cultural, social and narrative aspects in the temporal context of the series (1987-1990) in New York, which stands out not only as an entertainment series, but as an important voice in promoting diversity, equality and acceptance. It offers a broad view of the experiences of marginalized communities in New York, as they struggle to communicate their causes, even without full knowledge of communication. Therefore, it is a full analysis of the entire North American production, aiming to generally address the historical, social, economic and political context of the series, identifying the communications of cause within its episodes, as well as addressing the communication of causes and their concepts until their execution, and highlight the importance of public relations for effective communication.